2020
DOI: 10.1159/000509216
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Implications of Physical Inactivity among Older Adults during the COVID-19 Pandemic

Abstract: Social distancing has been adopted worldwide to control severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission. Social isolation is likely to lead to a decline in physical activity, which could result in immune system dysfunction, thereby increasing infection susceptibility and exacerbating the pathophysiology of conditions that are common among older adults, including cardiovascular disease, cancer, and inflammatory disorders. Older adults and people living with these comorbidities are at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 44 publications
1
95
0
26
Order By: Relevance
“…Therefore, for the elderly population, physical activity is even more essential, as these individuals generally have greater comorbidities and, in relation to the new coronavirus, are more vulnerable to contracting the disease [69]. Damiot et al [70] suggested that individuals who have remained active throughout their lives have less pronounced immunosenescence characteristics, which may be a possible protective factor against the development of complications caused by In this sense, beneficial effects of regular physical exercise have been reported in the elderly population, including reduction in oxidative stress, improvement in immune competence and reduction in cellular changes related to immunosenescence [13,16]. Elderly individuals who maintain continued physical activity have levels of TCD4 + and TCD8 + lymphocytes similar to younger individuals, in addition to not having harmful defects in the recruitment of lymphocytes during the infectious process [58].…”
Section: Physical Exercise and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, for the elderly population, physical activity is even more essential, as these individuals generally have greater comorbidities and, in relation to the new coronavirus, are more vulnerable to contracting the disease [69]. Damiot et al [70] suggested that individuals who have remained active throughout their lives have less pronounced immunosenescence characteristics, which may be a possible protective factor against the development of complications caused by In this sense, beneficial effects of regular physical exercise have been reported in the elderly population, including reduction in oxidative stress, improvement in immune competence and reduction in cellular changes related to immunosenescence [13,16]. Elderly individuals who maintain continued physical activity have levels of TCD4 + and TCD8 + lymphocytes similar to younger individuals, in addition to not having harmful defects in the recruitment of lymphocytes during the infectious process [58].…”
Section: Physical Exercise and Covid-19mentioning
confidence: 99%
“…A low presence of circulating pro-inflammatory cytokines is observed in contrast to the increase in anti-inflammatory cytokines. Thus, there are positive changes in the immune system of these individuals, including enhancements in host response and vaccine immunoprotection [70].…”
Section: Physical Exercise and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The most convenient of such interventions are not the still underdeveloped regimens of using the anti-aging drugs according to the “geroscience” agenda ( Nir Barzilai et al, 2020 ; Promislow, 2020 ), but the immediately available commencing to adequate physical and mental activities ( Thune and Furberg, 2001 ; Gleeson et al, 2011 ; Lee et al, 2017 ; Celis-Morales et al, 2019 ; Kenyon, 2020 ; Neto et al, 2020 ) and involvement in social interactions ( Yang et al, 2016 ; Kikusui, 2018 ; Banerjee et al, 2020 ; Santini et al, 2020 ). Physical exercises are clearly beneficial for endothelial functions, including those that hinge on the nitric oxide (see above) and RASs ( Evangelista, 2020 ), as well as for immunity ( Damiot et al, 2020 ). Specific regimens of exercises accounting for the peculiarities of the current epidemiological situation are being developed and tested ( Dominski and Brandt, 2020 ; Ravalli and Musumeci, 2020 ; Zhu, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This constant flow of information about the Pandemic could be a source of anxiety and stress for the aged. The older people's continual exposure to the daily news as the media houses announce the mortality rate makes it uncomfortable for them, resulting in anxiety (Damiot et al, 2020). This constant information could also cause sleep disturbance and low mood among elderly individuals, which could have a detrimental effect on life quality.…”
Section: Covid-19 Information Affecting the Older Personsmentioning
confidence: 99%